2010
DOI: 10.1088/0964-1726/19/4/045016
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic energy harvesting by piezoelectric curved beams in the cavity of a sonic crystal

Abstract: Acoustic energy harvesting by piezoelectric curved beams in the cavity of a sonic crystal is investigated. A resonant cavity of the sonic crystal is used to localize the acoustic wave as the acoustic waves are incident into the sonic crystal at the resonant frequency. The piezoelectric curved beam is placed in the resonant cavity and vibrated by the acoustic wave. The energy harvesting can be achieved as the acoustic waves are incident at the resonant frequency. A model for energy harvesting of the piezoelectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 27 publications
0
53
1
Order By: Relevance
“…Acoustic energy is another potential source for power generation. The increasing research studies about acoustic energy harvesting have been reported [12][13][14][15][16][17][18]. The Helmholtz resonator is widely used in the acoustic energy harvester systems since it can largely amplify the acoustic pressure in its cavity [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acoustic energy is another potential source for power generation. The increasing research studies about acoustic energy harvesting have been reported [12][13][14][15][16][17][18]. The Helmholtz resonator is widely used in the acoustic energy harvester systems since it can largely amplify the acoustic pressure in its cavity [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The amplified cavity pressure drives the vibration of the piezoelectric plate mounted on the back plate or in the cavity of Helmholtz resonator, the electric energy is thus induced by the piezoelectric effect. On the other hand, the sonic crystal configuration has also been exploited in acoustic energy harvesting [16][17][18]. Owing to the acoustic wave localization effect inside the sonic crystal cavity, the cavity pressure is greatly magnified to deform the piezoelectric material.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, little effort has been given to exploit the energy of traveling waves in fluids and structures. Only a few research groups have studied this area with a focus on polarization-patterned piezoelectric solids [17], quarter-wavelength resonators [18], Helmholtz resonators [19][20] and phononic crystals [21][22][23][24]. In addition, Yang et al [25] combined the sonic crystal concept with the Helmholtz resonators to enhance the acoustic energy harvesting.…”
Section: Introductionmentioning
confidence: 99%
“…Printed batteries can be incorporated into the system, but have limited capacity in thin form factors, necessitating eventual replacement or recharging. To overcome this issue, energy harvesting approaches can be used, including using energy provided by thermal [14], [15], optical [16], mechanical [17], acoustic [18] or radiofrequency (RF) [19] sources. RF energy harvested from a dedicated source is of particular interest as it allows for a simplified system that can function in a wide range of environments, and can be addressed using readily available readout devices.…”
mentioning
confidence: 99%